A Novel Immunomodulator Delivery Platform Based on Bacterial Biomimetic Vesicles for Enhanced Antitumor Immunity. Issue 43 (12th September 2021) - Hua, Liangqun; Yang, Zhongqian; Li, Weiran; Zhang, Qishu; Ren, Zhaoling; Ye, Chao; Zheng, Xiao; Li, Duo; Long, Qiong; Bai, Hongmei; Sun, Wenjia; Yang, Xu; et al.
Abstract: T cell activation‐induced cell death (AICD) during tumor pathogenesis is a tumor immune escape process dependent on dendritic cells (DCs). Proper immune‐modulatory therapies effectively inhibit tumor‐specific CD8 + T cell exhaustion and enhance antitumor immune responses. Here, high‐pressure homogenization is utilized to drive immunomodulator IL10‐modified bacteria to extrude through the gap and self‐assemble into bacterial biomimetic vesicles exposing IL10 (IL10‐BBVs) on the surface with high efficiency. IL10‐BBVs efficiently target DCs in tumor‐draining lymph nodes and thus increase the interaction between IL10 on BBVs and IL10R on DCs to suppress AICD and mitigate CD8 + T cell exhaustion specific to tumor antigens. Two subcutaneous peripheral injections of IL10‐BBVs 1 week apart in tumor‐bearing mice effectively increase systemic and intratumoral proportions of CD8 + T cells to suppress tumor growth and metastasis. Tumor‐specific antigen E7 is enclosed into the periplasm of IL10‐BBVs (IL10‐E7‐BBVs) to realize concurrent actions of the immunomodulator IL10 and the tumor antigen human papillomavirus (HPV) 16E7 in lymph nodes, further enhancing the antitumor effects mediated by CD8 + T cells. The development of this modified BBV delivery platform will expand the application of bacterial membranes and provide novel immunotherapeutic strategies for tumor treatment. Abstract : Immunomodulator interleukin 10 (IL10) exposed on the surface and tumor antigen E7 packaged in the periplasm (IL10‐E7‐bacterial biomimetic vesicles (BBVs)) are constructed using a BBV modification technique. After IL10‐E7‐BBV injection, E7 induces specific tumor immunity, while IL10 reduces CD8 + T cell exhaustion in lymph nodes. Therefore, multifunctional synergy is achieved in a drug design to enhance tumor immunity.